Management of Innovative Behaviour of Human Resources - Bieliakova, Oksana; Onishchenko, Vladyslav; Ustynov, Roman; Kazak, Ðžlena (International Journal of Engineering and Technology, 2018)
The purpose of the research is to manage the innovative activity of human resources. In order to achieve this goal, the procedure and components of such an analysis were determined. The directions of research of state of management of innovative activity of human resources are established. These include: analysis of human resources, analysis of conditions that ensure the implementation of such management and analysis of the economic efficiency of the enterprise. The factors influencing each of these directions of estimation of the state of management of innovative activity of human resources are grounded and systematized. Investigating the manifestation of these factors provides an opportunity to objectively assess how human resources management is effective and consistent with the innovative development of the enterprise. This approach also allows comparing best practices in human resource management. The definition of factors serves as the basis for forming an approach to a comprehensive assessment of the state of innovation activity management of human resources. The methodology for assessing the state of management of human resource innovation activity on the basis of rating is a new tool in this area. In addition, unlike existing assessments, it combines management, production and management of human resources. It was emphasized that human resources are the main factor of innovation development of the enterprise. The step-by-step procedure for assessing the state of innovation activity management of human resources is presented. The scale for analysis of the obtained evaluation results is proposed. It is noted that there is a need for further detailing the results to determine measures to improve the situation for a particular company. Approbation of the methodology of such an assessment of the state of innovation activity management of human resources for the seaports of the Black Sea-Azov basin was conducted.Â Â Â
Keywords: innovative activity; human resources; rating estimation; seaports; human resources management.